Does Community Radio Functions Truly? : As an Autonomous Sphere? Study on its Status in South Asia - Rasmin, M.C.; Raguram, S. (Sri Lanka Development Journalist Forum, 2019)
Community Radio (CR) in South Asia has been thriving with a unique identity as result of collective activism and lobbying by various stakeholders, including practitioners, civil society activists, academia, media freedom fighters, international agencies and several others. Nepal became the first country, in South Asia, to liberate the airwaves for the use of community with the inception of Radio Sagarmatha. Presently, around 350 CR stations are functioning in various parts of Nepal. The CR agenda in India, was mostly led by a activists and individuals. Around 217 CR stations are functioning in India. The revised CR policy guideline (2006) in India provides scope for both academic and local NGOs to receive CR lisence. However, the ability of Indian CR stations to air news and current affairs programs is legally challenged. The advocacy for CR in Bangladesh was initiated in early 1998, but it took a decade for local organizations to gain legal recognition. Presently, 18 CR stations are functioning in Bangladesh where CR largely facilitate a development goal. . In general, CR in South Asia has been flourishing for the last three decades. However, it is widely believed that CR, in the region has failed to gain its own autonomy despite its long history of existence. This study attempts to understand as to what extent the CR in the region – in Nepal, India and Bangladesh has been functioning as a truly autonomous sector.